Sugarite Coal Camp. - Veltri, Patricia ([S.l.] : Arcadia Publishing, 2018)
Tucked into a remote canyon in northeastern New Mexico, Sugarite Coal Camp created a true melting pot for mostly immigrant miners from Eastern Europe, Italy, Greece, Scotland, Wales, Ireland, Mexico and even Japan. Providing coal for several states for decades, the mine was developed by the St. Louis, Rocky Mountain and Pacific Company in the early 1900s. Mining families were poor, but community was strong. Today, visitors to Sugarite Canyon State Park tour ghostly remains of the camp, one of the few accessible to the public.
Forward by Mickey Baker.
106169
Keywords: Patricia Veltri; Patricia H. Walsh; Mining camps. -- Coal. -- Pictoral works with text. -- Northeastern New Mexico - Coxfax County